A water management investment decision-support tool developed by WLE/CIAT in Honduras was expanded to other Central American countries and is being disseminated to nine new countries - CGIAR Research Program on Water, Land and Ecosystems (2021)
The "Agua de Honduras" platform, initially developed and piloted in western Honduras, is now an indispensable decision-support system for the south of the country as well. While it is being extended to facilitate water planning in the country's main basins with new flood analyses and capabilities, AGRI (AGua para RIego), its most attention-grabbing tool, has now been extended into other Central American countries, and is being adapted for application in Latin America, Africa and the Caribbean.